Challenges for the Development of Cycling as Sustainable Mobility - Arnaudov, Borislav (Research Papers, 2025)
Cycling should be an essential part of Sofia's integrated urban development and transport policy. In countries such as the Netherlands, Denmark, Sweden and Germany, public authorities are increasingly looking at cycling as an excellent means of alleviating environmental problems, congestion, and improving road safety. Prioritizing bicycles as a daily means of transport in Sofia is an effective and inexpensive strategy that will help the capital to meet its green growth targets and at the same time meet its zero net emissions commitments. The purpose of this report is to look at the key aspects that encourage modal shift and that strengthen the position of cycling as a cost-effective policy option for improving Sofia's air quality, and more importantly, for meeting the air quality targets set by European legislation.
Keywords: Sustainable mobility; Cycling; Cycling infrastructure; Safe system